2008
DOI: 10.4049/jimmunol.180.6.4098
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pulmonary T Cell Response to Helper-Dependent Adenoviral Vectors following Intranasal Delivery

Abstract: In spite of the extensive research in the field of gene therapy, host immune responses continue to be the major barrier in translating basic research to clinical practice. Helper-dependent adenoviral (HD-Ad) vectors show great potential for pulmonary gene therapy, but the knowledge of pulmonary immune responses toward these vectors is very limited. In this study, we show that HD-Ad vectors are potent stimulators of dendritic cell (DC) maturation, thus leading to stimulation of T cell proliferation with ∼6% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…This reduction is the likely reason that transgene expression is more persistent than that observed for early rAd vectors, but as the reduction is not absolute the risks of immune system surveillance increase upon re-administration which might result in cessation of transgene expression [33]. Encouragingly, recent work has shown that HD-Ad can be used to successfully transduce respiratory tissue in mice, pigs and human airway cultures [34].…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…This reduction is the likely reason that transgene expression is more persistent than that observed for early rAd vectors, but as the reduction is not absolute the risks of immune system surveillance increase upon re-administration which might result in cessation of transgene expression [33]. Encouragingly, recent work has shown that HD-Ad can be used to successfully transduce respiratory tissue in mice, pigs and human airway cultures [34].…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…Bone marrow cells were isolated from tibia and femurs of adult mice and cultured in the presence of GM-CSF for 7 days as described previously [34]. Isolation of naïve CD4 1 CD25 -T cells Naïve CD4 1 CD25 -CD62L 1 T cells were isolated from spleens of mice using CD4 1 CD62L 1 naïve T-cell isolation kit in conjunction with MACS columns from Miltenyi Biotec (Auburn, CA), following the manufacturer's instructions.…”
Section: Generation Of Bone-marrow-derived DCmentioning
confidence: 99%
“…Necrosis was induced by pelleting cells followed by three cycles of freeze and thaw. Similar protocol was used for the induction of splenocyte apoptosis, which was isolated from spleens of C57BL/6 mice as described previously [34].…”
Section: Induction Of DC Apoptosis and Necrosismentioning
confidence: 99%
See 2 more Smart Citations